Analisis Efektivitas Penggunaan Teks Anekdot dalam Pembelajaran untuk Pengembangan Elemen Pengetahuan dan Keterampilan Proses pada Peserta Didik SMA - Syaadah, Aminatus; Saputra, Bachtiar Adi (Lembaga Yasin AlSys, 2024)
This research aims to analyze the effectiveness of using anecdotal texts in learning at the Senior High School (SMA) level with a focus on developing elements of knowledge and process skills in students. The research method involves a pre-post test experimental design with a control group and an experimental group. The sample for this research consisted of students from SMA Muhammadiyah 1 Taman who received anecdotal text material. The research variables focus on developing students' knowledge elements and process skills. Anecdotal material is presented through various media, including learning videos, anecdotal images, and audio-visual texts. Students are given student worksheets (LKPD) to support their understanding of anecdotal material. The results of the research show that the use of anecdotal texts in learning is effective in developing students' knowledge elements and skill elements. Students can provide explanations regarding anecdotal material from learning videos, anecdotal images and audio-visual texts. Apart from that, students' involvement in the learning process increases along with the implementation of LKPD which supports their understanding of anecdotal texts. These findings provide an important contribution to the development of learning methods that focus on anecdotal texts at the high school level. The practical implications of this research can be applied in curriculum development and teaching strategies to increase students' understanding and involvement in learning anecdotal texts. Future research could explore additional aspects of the use of anecdotal texts in learning to further deepen understanding of their contribution to the development of students' knowledge and process skills.